2015
DOI: 10.1155/2015/729017
|View full text |Cite
|
Sign up to set email alerts
|

Polydatin Inhibits Formation of Macrophage-Derived Foam Cells

Abstract: Rhizoma Polygoni Cuspidati, a Chinese herbal medicine, has been widely used in traditional Chinese medicine for a long time. Polydatin, one of the major active ingredients in Rhizoma Polygoni Cuspidati, has been recently shown to possess extensive cardiovascular pharmacological activities. In present study, we examined the effects of Polydatin on the formation of peritoneal macrophage-derived foam cells in Apolipoprotein E gene knockout mice (ApoE−/−) and explored the potential underlying mechanisms. Peritonea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 38 publications
1
17
0
Order By: Relevance
“…Pharmacological studies in the past decade have shown that polydatin exhibits a broad range of bioactivities with cardiovascular relevance, including antioxidation, anti-inflammation, cardioprotection, blood vessel dilation, lipid-lowering effect, as well as inhibitory effects on platelet aggregation, monocyte adhesion to activated endothelium, thrombus formation, and atherosclerosis development (Du et al, 2009;Deng et al, 2011;Liu et al, 2012b;Ma et al, 2016;Gugliandolo et al, 2017). The preventive effects of polydatin on foam cell formation were reported recently (Wu et al, 2015b). Polydatin treatment of 48 hours reduced the level of TC, FC, and CE, together with reducing the secretion of TNF-a and IL-1b in oxLDL-stimulated ApoE 2/2 mouse macrophages.…”
Section: B Terpenoidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pharmacological studies in the past decade have shown that polydatin exhibits a broad range of bioactivities with cardiovascular relevance, including antioxidation, anti-inflammation, cardioprotection, blood vessel dilation, lipid-lowering effect, as well as inhibitory effects on platelet aggregation, monocyte adhesion to activated endothelium, thrombus formation, and atherosclerosis development (Du et al, 2009;Deng et al, 2011;Liu et al, 2012b;Ma et al, 2016;Gugliandolo et al, 2017). The preventive effects of polydatin on foam cell formation were reported recently (Wu et al, 2015b). Polydatin treatment of 48 hours reduced the level of TC, FC, and CE, together with reducing the secretion of TNF-a and IL-1b in oxLDL-stimulated ApoE 2/2 mouse macrophages.…”
Section: B Terpenoidsmentioning
confidence: 99%
“…Reduced TC, FC, CE, together with reduction of secretion of TNF-a and IL-1b in oxLDLstimulated ApoE 2/2 mouse macrophages (Wu et al, 2015b). Polydatin improved dyslipidemia via suppressing PCSK9 and upregulation of hepatic LDLR expression (Li et al, 2018a).…”
Section: Polydatinmentioning
confidence: 99%
“…Moreover, PD inhibited aPM 2.5 -induced inflammation, reducing infiltration, maintaining alveoli structure, preventing ceramide chaos and inhibiting inflammatory cytokines (TNF-α and IL-1β) production in the lung41. These defense mechanisms might involve the regulation of the Nrf-2 and PPAR-γ pathways1542. For BAL protein production and weight change the PD protection was observed but not at significant level.…”
Section: Discussionmentioning
confidence: 94%
“…The process of cholesterol efflux involves the ATP-binding cassette (ABC) transporter A1 (ABCA1), ABCG1 and BI-receptor scavenger (SR-BI) [23,24]. Disruption in the process of cholesterol efflux results in cholesterol accumulation in macrophages [25], whereas ABCA1 stimulation can inhibit foam cell formation [26].…”
Section: Discussionmentioning
confidence: 99%